The Effect of Webcomics as Media on Students' Writing Achievement in Narrative Text - R. A. Tri Ratu Utami; Hamzah Hamzah (JEELS (Journal of English Education and Linguistics Studies), 2025)
Webcomics, a unique form of comics disseminated exclusively through internet platforms, have garnered attention for their interactive nature and potential to enhance student engagement. This experimental study aimed to investigate the effect of utilizing webcomics on eighth-grade students' writing achievement compared to traditional methods. The study employed an experimental design with an experimental group exposed to webcomics and a control group taught through non-webcomics. The sample comprised 8.3 as the experimental class and 8.4 as the control class. Placement test and post-tests, including placement tests and post-test assessments, were administered to measure writing proficiency. Statistical analysis, specifically independent sample t-tests, revealed a significant difference in writing achievement between the experimental and control groups (p = 0.006), indicating the effectiveness of webcomics in enhancing students' narrative writing skills. This finding underscores the importance of innovative pedagogical approaches in fostering student success and highlights the evolving landscape of education. Webcomics emerge as a promising tool for educators seeking to promote meaningful learning experiences and engage students in narrative text writing. Keywords: Webcomics, media in writing, writing achievement, narrative text, genre-based approach